THE IMPLEMENTATION OF E-JAS SCIENCE EDUTAINMENT TO IMPROVE ELEMENTARY SCHOOL STUDENT’S CONCEPTUAL UNDERSTANDING - Ardianti, Sekar Dwi; Wanabuliandari, Savitri; Rahardjo, Susilo (Unnes Science Education Journal, 2019)
This research aims to unveil the improvement of elementary school student’s conceptual understanding through the implementation of E-Jas Science Edutainment. This research is a pre-experimental research with the design of one group pretest and posttest. The sample of the research uses purposive sampling technique. The result of the Normalized-Gain research shows that there is an improvement of student’s achievement under the criteria of medium (28.57%) and high (71.43 %). The classical result shows the normalized gain of 71% or 0.71, which means that student’s improvement was really high. The result shows that the implementation of E-JAS Science Edutainment can improve student’s learning achievement.